2012
DOI: 10.1158/0008-5472.can-11-3990
|View full text |Cite
|
Sign up to set email alerts
|

The Oncogenic Lung Cancer Fusion Kinase CD74-ROS Activates a Novel Invasiveness Pathway through E-Syt1 Phosphorylation

Abstract: Patients with lung cancer often present with metastatic disease and therefore have a very poor prognosis. The recent discovery of several novel ROS receptor tyrosine kinase molecular alterations in non-small-cell lung cancer (NSCLC) presents a therapeutic opportunity for the development of new targeted treatment strategies. Here, we report that the NSCLC-derived fusion CD74-ROS, which accounts for 30% of all ROS fusion kinases in NSCLC, is an active and oncogenic tyrosine kinase. We found that CD74-ROS express… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(60 citation statements)
references
References 32 publications
2
58
0
Order By: Relevance
“…We also identified multiple c-ros oncogene 1 ( ROS1 ) fusions, including ROS1 fusions in 8/513 lung adenocarcinomas, all of which have been previously described9101112. In addition, we detected a CEP85L – ROS1 fusion in a glioblastoma tumour sample (Fig.…”
Section: Resultsmentioning
confidence: 75%
“…We also identified multiple c-ros oncogene 1 ( ROS1 ) fusions, including ROS1 fusions in 8/513 lung adenocarcinomas, all of which have been previously described9101112. In addition, we detected a CEP85L – ROS1 fusion in a glioblastoma tumour sample (Fig.…”
Section: Resultsmentioning
confidence: 75%
“…Previously we demonstrated that ROS1 fusion kinases preferentially signal through the tyrosine phosphatase Src homology-2 domain containing protein tyrosine phosphatase-2 (SHP2) and activate both the MEK1/2-ERK1/2 and the AKT/mTORC1 signaling axes (32,33). Therefore, we evaluated the impact of PF-06463922 on these pathways.…”
Section: Pf-06463922 Potency In Cells Expressingmentioning
confidence: 99%
“…The downstream signalling cascade is achieved by navigating through phosphoinositide 3 kinase/mammalian target of rapamycin pathway, phosphorylation/activation of signal transducers and activators of transcription 3 (STAT3) and vav 3 guanine nucleotide exchange factor 1 eventually leading to regulation of anchorage-independent cellular growth and cell morphology 8 12–16. Interestingly, in a recent report, Jun et al demonstrated that the activation of downstream signalling pathways differ based on fusion partners of ROS1, as phosphorylation/activation of E-Syt1 (extended synaptotagmin 1) led to an invasive phenotype in CD74-ROS1 transduced cells, but not in FIG-ROS1 transduced cells 15 Figure 2. summarises14 the key downstream signalling pathways known to be involved in downstream cell proliferation, survival, migration and metastasis, transformation and invasiveness 8 14…”
Section: Ros1 Signalling Pathwaymentioning
confidence: 98%